Resistance to veterinary antimicrobials of Staphylococcus aureus from mastitic milk. (20th October 2021) - Rossi, F; Marino, L; Pomilio, F; Centorotola, G; Cornacchia, A; Perilli, M; Scattolini, S; Telera, GC; Del Matto, I
Abstract: Background: Use of antimicrobials in veterinary medicine for prophylactic and therapeutic purposes is one of the main culprits for the selection of antimicrobial resistant bugs that currently threaten human and animal health. Therefore, surveillance on antimicrobial resistance (AMR) selection trends in animal husbandry is of utmost importance to prevent the spread of resistant bugs to humans. The species Staphylococcus aureus (Sa), that is of particular concern for the spread of methicillin-resistant (MRSA) strains, often causes mastitis in milk producing animals, thus requiring antibiotic treatment that can impact on the AMR status of this pathogen. With the aim of elucidating the current evolution of AMR in Sa involved in mastitis and the threats posed by the consumption of raw milk or inadequately pasteurized dairy products, data from antimicrobial susceptibility testing carried out on Sa strains from mastitis in years 2013 - 2019 in Molise region, Italy, were analyzed. Methods: Sa isolates were tested by disk diffusion and inhibition halo sizes were converted in Minimum inhibitory concentrations (MIC) according to the EUCAST standards for the antibiotics there included. One isolate per AMR profile per farm was considered to define the percentage of the antibiotic resistant on the total number of isolates per year. Results: The number of diagnosed Sa infections per year ranged between seven and nineteen, with a total of 78 isolates from 70 farms. The percentages of those resistant to aminoglycosides kanamycin, neomycin and paromomycin, to the macrolide tylosin and the multi drug resistant (MDR) isolates increased since 2015. The latter ranged between 26.3 and 85.7%. Conclusions: AMR and MDR Sa in milk producing animals pose a serious risk to public health and needs stricter surveillance. Key messages: Limiting use of antibiotics is needed to revert the trend. AMR Sa strains in dairy products, need to be kept under control for the strict connection with human health.